3 Screen ELISA for High-Throughput Detection of Beta Cell Autoantibodies in Capillary Blood - Ziegler, Anette-G; Haupt, Florian; Scholz, Marlon; Weininger, Katharina; Wittich, Susanne; Löbner, Stephanie; Matzke, Claudia; Gezginci, Cigdem; Riethausen, Stephanie; Beyerlein, Andreas; Zillmer, Stephanie; Amoroso, Marie; et al. (Diabetes technology & therapeutics, 2016)
Testing for beta cell autoantibodies is used for wide-scale identification of early stages of type 1 diabetes. This requires suitable screening assays. We aimed to establish screening that utilized a first step assay (3 Screen) able to detect autoantibodies to the target antigens glutamic acid decarboxylase-65 (GAD), insulinoma-associated antigen 2 (IA-2), and zinc transporter 8 (ZnT8) to identify children positive for multiple beta cell autoantibodies. An ELISA format was used where plates were coated with a mixture of recombinant GAD, IA-2, and ZnT8 W/R-dimer molecules. The performance was determined in venous blood from 686 first-degree relatives of patients with type 1 diabetes, and 200 patients at onset of type 1 diabetes, and applied as a screening assay in capillary blood from 33,639 general population children. The 3 Screen assay sensitivity for detecting autoantibody-positive patients at onset of type 1 diabetes was similar to that achieved by separate radiobinding assays (RBAs) for antibodies to GAD, IA-2, and ZnT8. Results in venous and capillary serum were correlated (R = 0.987). At a threshold corresponding to the 98th centile (29.1 U/mL) of all 33,639 capillary samples, the 3 Screen was positive in 123 samples with two or more RBA-positive antibodies to insulin, GAD, IA-2, or ZnT8, 146 with one antibody, and 479 that were RBA negative for beta cell autoantibodies. A 3 Screen ELISA was developed that was suitable for first step screening of multiple beta cell autoantibodies in capillary blood.